A lower psoas muscle index predicts a poorer prognosis in metastatic hormone‐naïve prostate cancer. Issue 1 (13th August 2020) - Iwamoto, Genta; Kawahara, Takashi; Miyai, Toshitaka; Yasui, Masato; Hasumi, Hisashi; Miyoshi, Yasuhide; Yao, Masahiro; Uemura, Hiroji
Abstract: Introduction: A recent investigation revealed that sarcopenia was associated with a poorer prognosis in some solid malignancies, including prostate cancer. In most reports, sarcopenia was defined as a low psoas volume on CT. This study investigated the association of sarcopenia, determined according to the psoas muscle volume and density on CT, with the prognosis in patients with metastatic hormone‐naïve prostate cancer (mHNPC). Methods: A total of 66 patients initially diagnosed with mHNPC were enrolled in this study. Skeletal muscle was evaluated according to the psoas muscle index density (PMID) on computed tomography scans. The psoas muscle volume was calculated at the level of L3 and CT density was evaluated as the mean CT density at the psoas muscle area. We divided the patients into higher and lower PMID groups. Results: The lower PMID group (on both sides) showed a poorer overall survival than the higher PMID group (Right: 32.5 vs 99.0 months in Rt PMID, P = .014; Left: 36.0 vs 100.0 months in Lt PMID, P = .029). The lower PMID group (on both sides) showed a shorter time to CRPC (Right: 9.0 vs 42.0 months in Rt PMID, P = .006; Left: 9.0 vs 31.0 months in Lt PMID, P = .005). A multivariate analysis showed that lower Rt PMID and Lt PMID were independent risk factors for poorer OS (HR:2.02, 95%CI: 1.04‐3.90, P = .037, HR:2.29, 95%CI: 1.18‐4.47, P = .015, respectively). For CRPC, both Rt and Lt lower PMID also showed independent risk factors for shorter time to CRPC (HR:2.39, 95%CI: 1.23‐4.62, P = .010, HR:2.43, 95%CI: 1.23‐4.78, P = .010, respectively). Conclusions: Among mHNPC patients, both lower PMID groups showed a poorer overall survival and shorter time to CRPC than the higher PMID groups.